Subjective satisfaction in long-term orthokeratology patients - Santolaria Sanz, Elena (2013)
Purpose: To AU3 evaluate the subjective satisfaction in visual stability, night vision complains, and light distortion phenomena, and also the number of hours and days per week of lens wear, in patients with myopia undergoing orthokeratology (OK) treatment for at least 1 year. Methods: A visual analog scale (VAS) questionnaire containing 18 items was administered to 44 patients, 29 women and 15 men (mean age, 24.39 6 9.11 years), with a baseline spherical equivalent refractive error of 22.40 6 0.94 diopters and astigmatism up to 20.5 diopters. Average treatment period by the time of data collection was 19 6 7 months. Patients rated their satisfaction with the correction, with complaints of visual distortion being graded on a scale of 0 to 10, where 0 indicated no discomfort at all. Results: More than 50% of patients skipped lens wear at least 1 night per week. The most common wearing pattern was 6–8 hours a day for 72.7% with 54.5% of patients wearing lenses every 2–3 nights only. Subjective vision scores after lens removal was 9.1 6 1.1 after having worn the lenses and 8.1 6 1.4 after skipping lens wear for 1 night. Subjective vision scores before lens insertion at the end of the day was 6.9 6 2.0 and 5.8 6 2.4, respectively. The number of hours until noticeable blur reduced with increased level of baseline myopia (r = 0.396; P , 0.001). Conclusion: Orthokeratology patients show an irregular wearing pattern after 1 year of treatment that has significant effects on the subjective visual performance over the next day of skipping lens wear. Light distortion under low-light conditions seems to be a transient complication of the treatment and most of the patients report an improvement after the first weeks of treatment.